PEDAGOGICAL TECHNOLOGY OF SELECTION OF SCHOOLCHILDREN BY TYPES OF ATHLETICS - Jamshid Eshpulatov (Journals Park Publishing, 2023)
The creation of the "Children's Sports Development Fund" is of great practical importance for the upbringing of the younger generation as a healthy and harmonious person. Today, about 2 million children in our country are engaged in more than 30 sports. They become healthy, strong, brave and persistent. The development of children's sports serves as an important tool in achieving physical and spiritual maturity of the youth of our country. The athletics sport included in the Olympic program is developing more and more in our country and is becoming popular among boys and girls.
Keywords: Children's and adolescent sports schools, Organization of athletics classes, selection of short-distance runners for the preparatory stage.